Pembuatan Buku Pedoman Pengelolaan Perpustakaan Sekolah di SMA N 1 Painan - Permata, Ryska Dian; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discusses the making of a school library management manual in SMA N 1 Painan. The purpose of writing this paper is to know the process of library management in SMA N 1 Painan. The creation of this management guidebook aims to provide information to the librarian in managing the library.The method used is the method of observation. Data were collected through interviews with librarians and field surveys, based on the facts that occurred in the field at SMA N 1 Painan. Observations were made for 14 days.Based on the result of the research, it can be concluded that the making of library management guide book is to help librarians in managing school library well. With the book management of school libraries in SMA N 1 Painan, can advance the school library tersebut.Pada school library management manual in SMA N 1 Painan can be concluded steps of library management manual book making that is (1) needs analysis, based on the needs of librarians in Managing the school library and also explained about how the procedures and techniques for making library supporting tools; (2) product design to know what items will be described in the library management manual; (3) making of product, done starting from activity of collecting data and information then arranging framework of writing until product making process.Keywords : Managing library, handbook, school library